Carrier-free talcum powder particles and preparation method thereof
Through the multi-graft copolymerization reaction of carrier-free talc powder particles, the problems of unstable molding of talc powder particles and poor affinity of resin are solved, stable molding and high lipophilic dispersion are achieved, and dust pollution and production costs are reduced.
Patent Information
- Application Number
- CN202310054357.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-03
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-02-03
AI Technical Summary
During the use of existing talc powder particles, there are problems such as unstable molding, fragile transportation, and poor resin affinity, resulting in poor versatility, high cost and dust pollution.
Carrierless talc powder particles are used to form a stable particle shape and improve the resin affinity through multivariate graft copolymerization reaction of cellulose, water-soluble acrylic monomer, acrylate monomer and olefin silane coupling agent.
The stability of particle forming is achieved, the affinity with the resin is enhanced, the dust pollution is reduced, and the material utilization rate and production cost-effectiveness are improved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of talcum powder particle reinforcing agents for plastics, rubber or films, and in particular to carrier-free talcum powder particles and a preparation method thereof. Background Art
[0002] As a tensile, bending and impact-resistant mechanical property enhancer, talcum powder has been widely used in plastics, rubber, films and other fields. Loose powder talcum powder is fluffy and light, and it is not easy to mix directly with granular resin. It often needs to be made into granules in advance before it can be used. At present, there are several ways to granulate talcum powder:
[0003] 1. Pre-mix talc and resin, and then extrude resin particles with high talc loading through an extruder. This is a talc particle with a resin carrier, also called talc masterbatch. Since the talc masterbatch contains 20% or even higher dosage of a specific resin carrier, the formula applicability of the masterbatch product in other types of resins is limited.
[0004] 2. Directly vacuuming and extruding the talc powder can obtain compacted talc powder with increased density, but it is difficult to obtain formed particles. It still needs to be made into talc masterbatch with resin for convenient use.
[0005] 3. Although talcum powder can be obtained by adding water to wet granulation and then drying, the talcum powder can be obtained in a carrier-free granular form, but the granules are not stable and can be easily broken into powder during transportation, feeding, mixing and other production links. It is impossible to mix the granules, causing dust pollution to the production workshop.
[0006] 4. Although the formed particles can be obtained by simply adding adhesives and modifiers on the basis of wet granulation, the particles are still not stable enough. The stacking layers are high during transportation and the bumpy vibration of the vehicle causes the particles to break. The powder breaking rate is high when the materials are lightly hit and collided during feeding and stirring. In addition, talcum powder is an inorganic non-metallic mineral with poor compatibility with resin organic bodies. Simply adding modifiers is difficult to effectively coat the surface of talcum powder, and the coating is not firm and easy to fall off, and even causes microscopic particles to stick together and agglomerate and difficult to disperse. It is impossible to effectively improve the affinity between inorganic powder and organic resin, and it is also unable to give full play to the performance of talcum powder.
[0007] In summary, among the talc powder particles prepared by the prior art, the talc powder masterbatch containing a resin carrier is limited by the type and content of the carrier, resulting in poor versatility and high cost; the compacted or densified talc powder without a carrier has particles that are not formed or are not firmly formed, and are easily broken into powder during production and use, failing to achieve the effect of particle-to-particle blending, and also causing dust pollution in the workshop. Whether it is talc powder particles with or without a carrier, the prior art has not been able to effectively improve the affinity of talc powder with resin, and the surface coating of talc powder is not firm and easy to fall off, and the product performance cannot be fully exerted. In view of this, it is necessary to provide a new carrier-free talc powder particle to solve the defects of the prior art. Summary of the invention
[0008] The technical problem to be solved by the present invention is: in order to effectively improve the affinity between the surface of talc powder particles and resin and to make the particles firmly formed, the present invention provides a carrier-free talc powder particle.
[0009] The technical solution of the present invention to solve the above technical problems is as follows:
[0010] The present invention provides a carrier-free talcum powder particle, which comprises the following components in parts by weight:
[0011] 1000 parts of talc powder, 1-3 parts of cellulose, 1-3 parts of water-soluble acrylic monomers, 3-13 parts of acrylate monomers, and 0.5-1 part of vinyl silane coupling agents.
[0012] The carrier-free talcum powder particles of the present invention have the following beneficial effects:
[0013] The carrier-free talcum powder particles provided by the present invention have cellulose ends of the copolymers intertwined and linked together through physical action, and have a stable particle shape; the organic copolymer is wrapped on the surface of the talcum powder and is not easy to fall off, which effectively improves the affinity between the surface of the talcum powder particles and the resin. Therefore, the formula in the resin has strong applicability, and the production links such as transportation, feeding, and stirring can maintain a good particle shape, achieve particle mixing, avoid workshop dust pollution, and the surface modified coating is firmly combined, and the lipophilic dispersibility is good, giving full play to the role of talcum powder as a mechanical property enhancer such as tensile resistance, bending resistance, and impact resistance.
[0014] Based on the above technical solution, the present invention can also be improved as follows.
[0015] Furthermore, the sedimentation particle size D50 of the talcum powder is less than 5 microns.
[0016] By adopting the above further scheme, it is ensured that the surface of talc powder has sufficient active hydroxyl groups to couple with the ends of silane coupling agents, while talc powder particles with a sedimentation particle size D50>5 microns are relatively coarse and are rarely used as mechanical property enhancers for rubber and plastic films.
[0017] Furthermore, the cellulose is any one of carboxymethyl cellulose, sodium carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, and methyl cellulose, or a mixture of any two or more thereof.
[0018] By adopting the above further solution, it is ensured that the cellulose ends of the copolymer are entangled and linked together through physical action, thereby maintaining the stable particle formation.
[0019] Furthermore, the water-soluble acrylic monomer is any one of acrylic acid, sodium acrylate, methacrylic acid, sodium methacrylate, acrylamide, and methacrylamide, or a mixture of any two or more thereof.
[0020] By adopting the above further scheme, the formed copolymer has suitable water solubility and can quickly penetrate and adsorb on the surface of talc to form a coating layer.
[0021] Furthermore, the acrylic acid ester monomer is any one of methyl acrylate, ethyl acrylate, butyl acrylate, dodecyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, dodecyl methacrylate, and octadecyl methacrylate, or a mixture of any two or more thereof.
[0022] By adopting the above further scheme, the formed copolymer has suitable resin compatibility and can be coated on the surface of talcum powder to form a lipophilic organic coating layer, thereby enhancing the affinity between the surface of talcum powder and the resin.
[0023] Furthermore, the vinyl silane coupling agent is any one of vinyl trimethoxy silane, vinyl triethoxy silane, and γ-methacryloxypropyl trimethoxy silane, or a mixture of any two or more thereof.
[0024] By adopting the above further scheme, the silane coupling agent end of the formed copolymer is fully coupled with the active hydroxyl group on the surface of talcum powder, the organic copolymer is firmly anchored on the surface of talcum powder, the stability of the combination between the surface of talcum powder and the organic coating layer is improved, the coating layer copolymer is not easy to fall off, and the product performance is more stable.
[0025] Furthermore, the initiator is any one of potassium persulfate, sodium persulfate, and ammonium persulfate.
[0026] According to the above further scheme, the free radicals released by the initiator under heat initiate the multi-component graft copolymerization reaction of cellulose, water-soluble acrylic monomers, acrylate monomers and olefinic silane coupling agents.
[0027] The present invention also provides a method for preparing the above-mentioned carrier-free talc particles, comprising the following steps:
[0028] Step 1, weigh the following raw materials in parts by weight respectively: 1000 parts of talc, 200-400 parts of water, 1-3 parts of cellulose, 1-3 parts of water-soluble acrylic monomer, 3-13 parts of acrylate monomer, 0.5-1 parts of vinyl silane coupling agent, and 0.05-0.1 parts of initiator;
[0029] Step 2: dissolving cellulose in 200-400 parts of water, adding an initiator, stirring and heating to 65-70° C., and then adding a water-soluble acrylic monomer and an acrylate monomer to obtain a cellulose grafted primary polymer;
[0030] Step 3, heating the primary polymer obtained in step 2 to 80-85° C. under stirring, adding an olefinic silane coupling agent when blue light appears, and copolymerizing for 15-30 minutes to obtain a copolymer emulsion;
[0031] Step 4: spray the copolymer emulsion obtained in step 3 onto the talc powder and mix evenly, extrude the hydrotalc powder particles through a granulator, and dry at 120-160° C. to obtain the carrier-free talc powder particles.
[0032] The carrier-free talcum powder particles prepared by the present invention have the following beneficial effects:
[0033] 1) Granulation and surface lipophilic modification are integrated, and the emulsion copolymer plays the dual role of molding retaining agent and lipophilic modifier, with high material utilization, low production cost and good product versatility;
[0034] 2) The particles are firmly formed and not easily broken during transportation, feeding and stirring. They can be blended with resin particles and can be dispersed again under the shear force of mixing and extrusion, without any powder polluting the environment.
[0035] 3) It has excellent resin affinity. The lipophilic copolymer is firmly coated on the surface of talcum powder and is not easy to fall off, which can give full play to the tensile, bending and impact resistance enhancement effects of talcum powder added to the resin. DETAILED DESCRIPTION
[0036] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0037] The present invention provides a carrier-free talcum powder particle, which comprises the following components in parts by weight:
[0038] 1000 parts of talc powder, 1-3 parts of cellulose, 1-3 parts of water-soluble acrylic monomers, 3-13 parts of acrylate monomers, and 0.5-1 part of vinyl silane coupling agents.
[0039] Note: In addition to the above components, other components commonly used in the art may also be included, such as an appropriate amount of water added during the granulation production process.
[0040] The principle of the carrier-free talcum powder particles of the present invention is:
[0041] In the present invention, cellulose, water-soluble propylene monomers, acrylate monomers, and olefinic silane coupling agents are subjected to multi-component copolymerization under the action of an initiator, and the formed copolymer has suitable water solubility and resin compatibility, and can quickly penetrate and adsorb on the surface of talcum powder to form a coating layer. In the process of extruding into particles, the cellulose ends of the copolymer are intertwined and linked together by physical action to keep the particle forming stable. Under high temperature drying, the copolymer coating layer itself undergoes chemical crosslinking, and its silane coupling agent end is coupled with the active hydroxyl group on the surface of talcum powder, and the organic copolymer is firmly anchored on the surface of talcum powder. Therefore, the carrier-free talcum powder particles of the present invention have both a stable particle shape and suitable resin compatibility, and the organic copolymer is wrapped on the surface of talcum powder and is not easy to fall off.
[0042] In summary, the carrier-free talcum powder particles provided by the present invention, the cellulose ends of the copolymers are intertwined and linked together through physical action, and have a stable particle shape; the organic copolymer is wrapped on the surface of the talcum powder and is not easy to fall off, which improves the affinity between the surface of the talcum powder particles and the resin. Therefore, the formula in the resin has strong applicability, and the production links such as transportation, feeding, and stirring can maintain a good particle shape, achieve particle mixing, avoid workshop dust pollution, and the surface modified coating is firm, and the lipophilic dispersibility is good, giving full play to the performance of talcum powder as a tensile, bending, and impact-resistant reinforcing agent.
[0043] Furthermore, the sedimentation particle size D50 of the talcum powder is less than 5 microns.
[0044] Note: D50 particle size is the particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50%. Its physical meaning is that particles with a particle size larger than it account for 50%, and particles with a particle size smaller than it also account for 50%. D50 is also called median diameter or median particle size.
[0045] By adopting the above further scheme, it is ensured that the surface of talc powder has sufficient active hydroxyl groups to couple with the ends of silane coupling agents, while talc powder particles with a sedimentation particle size D50>5 microns are relatively coarse and are rarely used as mechanical property enhancers for rubber and plastic films.
[0046] Furthermore, the cellulose is any one of carboxymethyl cellulose, sodium carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, and methyl cellulose, or a mixture of any two or more thereof.
[0047] By adopting the above further solution, it is ensured that the cellulose ends of the copolymer are entangled and linked together through physical action, thereby maintaining the stable particle formation.
[0048] Furthermore, the water-soluble acrylic monomer is any one of acrylic acid, sodium acrylate, methacrylic acid, sodium methacrylate, acrylamide, and methacrylamide, or a mixture of any two or more thereof.
[0049] By adopting the above further scheme, the formed copolymer has suitable water solubility and can quickly penetrate and adsorb on the surface of talc to form a coating layer.
[0050] Furthermore, the acrylic acid ester monomer is any one of methyl acrylate, ethyl acrylate, butyl acrylate, dodecyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, dodecyl methacrylate, and octadecyl methacrylate, or a mixture of any two or more thereof.
[0051] By adopting the above further scheme, the formed copolymer has suitable resin compatibility and can be coated on the surface of talcum powder to form an organic coating layer, thereby enhancing the affinity between the surface of talcum powder and the resin.
[0052] Furthermore, the vinyl silane coupling agent is any one of vinyl trimethoxy silane, vinyl triethoxy silane, and γ-methacryloxypropyl trimethoxy silane, or a mixture of any two or more thereof.
[0053] By adopting the above further scheme, the silane coupling agent end of the formed copolymer is fully coupled with the active hydroxyl group on the surface of talcum powder, the organic copolymer is firmly anchored on the surface of talcum powder, the stability of the combination between the surface of talcum powder and the organic coating layer is improved, the coating layer copolymer is not easy to fall off, and the product performance is more stable.
[0054] Furthermore, the initiator is any one of potassium persulfate, sodium persulfate, and ammonium persulfate.
[0055] According to the above further scheme, the free radicals released by the initiator under heat initiate the multi-component graft copolymerization reaction of cellulose, water-soluble acrylic monomers, acrylate monomers and olefinic silane coupling agents.
[0056] The present invention also provides a method for preparing the above-mentioned carrier-free talc particles, comprising the following steps:
[0057] Step 1, weigh the following raw materials in parts by weight respectively: 1000 parts of talc, 200-400 parts of water, 1-3 parts of cellulose, 1-3 parts of water-soluble acrylic monomer, 3-13 parts of acrylate monomer, 0.5-1 parts of vinyl silane coupling agent, and 0.05-0.1 parts of initiator;
[0058] Step 2: dissolving cellulose in 200-400 parts of water, adding an initiator, stirring and heating to 65-70° C., and then adding a water-soluble acrylic monomer and an acrylate monomer to obtain a cellulose grafted primary polymer;
[0059] Step 3, heating the primary polymer obtained in step 2 to 80-85° C. under stirring, adding an olefinic silane coupling agent when blue light appears, and copolymerizing for 15-30 minutes to obtain a copolymer emulsion;
[0060] Step 4: spray the copolymer emulsion obtained in step 3 onto the talc powder and mix evenly, extrude the hydrotalc powder particles through a granulator, and dry at 120-160° C. to obtain the carrier-free talc powder particles.
[0061] The principle of the preparation method of the carrier-free talcum powder particles of the present invention is:
[0062] In step 2, cellulose undergoes a preliminary graft polymerization reaction with water-soluble acrylic monomers and acrylic ester monomers under the action of an initiator at 65-70°C.
[0063] In step three, the temperature is raised to 80-85°C. When blue light appears, it means that further polymerization reaction has been initiated. At this time, adding olefinic silane coupling agent to participate in copolymerization can avoid hydrolysis and condensation of the silane coupling agent itself. The copolymerization reaction can be controlled for 15-30 minutes. If the time is too long, the polymerization chain will be too long and insoluble matter will be easily formed.
[0064] In step four, the copolymer emulsion has suitable water solubility and resin compatibility, and can quickly penetrate and adsorb on the surface of talc. Talcum powder with a moisture content of 15%-30% can be easily squeezed into water-containing particles by a granulator. The drying process of the talcum powder particles is also a lipophilic modification reaction process. At 120-160°C, the copolymer itself cross-links and wraps the talcum powder. The silane coupling agent end couples and combines with the active hydroxyl groups on the surface of the talcum powder. Finally, the copolymer is firmly anchored on the surface of the talcum powder, significantly enhancing the resin affinity of the talcum powder surface. In addition, after the water evaporates, the cellulose end of the copolymer can maintain the talcum powder particles in a stable shape through entanglement and hooking, and it is not easy to break in conventional drops and collisions, and can be redispersed in water or oil by ultrasound.
[0065] The carrier-free talcum powder particles prepared by the present invention have the following beneficial effects:
[0066] 1) Granulation and surface lipophilic modification are integrated, and the emulsion copolymer plays the dual role of molding retaining agent and lipophilic modifier, with high material utilization, low production cost and good product versatility;
[0067] 2) The particles are firmly formed and not easily broken during transportation, feeding and stirring. They can be blended with resin particles and can be dispersed again under the shear force of mixing and extrusion, without any powder polluting the environment.
[0068] 3) It has excellent resin affinity. The lipophilic copolymer is firmly coated on the surface of talcum powder and is not easy to fall off, which can give full play to the tensile, bending and impact resistance enhancement effects of talcum powder added to the resin.
[0069] Embodiment 1:
[0070] As an example of the preparation method of the present invention, it comprises the following steps:
[0071] Step 1: Weigh the following raw materials in parts by weight respectively: 1000 parts of talc (D50 < 4 microns), 250 parts of water, 1.5 parts of sodium carboxymethyl cellulose, 1 part of acrylamide monomer, 4 parts of butyl methacrylate monomer, 0.5 parts of vinyl trimethoxy silane coupling agent, and 0.05 parts of potassium persulfate;
[0072] Step 2: dissolve sodium carboxymethyl cellulose in water, add potassium persulfate initiator, stir and heat to 65-70°C, then add acrylamide and butyl methacrylate monomers to obtain a cellulose grafted primary polymer;
[0073] Step 3: heating the primary polymer obtained in step 2 to 80-85° C. under stirring, adding a vinyl trimethoxy silane coupling agent when blue light appears, and copolymerizing for 15-30 minutes to obtain a copolymer emulsion;
[0074] Step 4: spray the copolymer emulsion obtained in step 3 onto talc powder and mix evenly, extrude water-containing talc powder particles through a granulator, and dry at 120-160° C. to obtain the carrier-free talc powder particles of the present invention.
[0075] Embodiment 2:
[0076] As an example of the preparation method of the present invention, it comprises the following steps:
[0077] Step 1: Weigh the following raw materials in parts by weight respectively: 1000 parts of talc (D50 < 2.5 μm), 300 parts of water, 2 parts of hydroxyethyl cellulose, 0.5 parts of methacrylic acid monomer, 1.5 parts of acrylamide monomer, 8 parts of butyl methacrylate monomer, 0.6 parts of γ-methacryloxypropyltrimethoxysilane, and 0.07 parts of sodium persulfate;
[0078] Step 2: dissolving hydroxyethyl cellulose in water, adding sodium persulfate initiator, stirring and heating to 65-70°C, and then adding acrylamide, methacrylic acid, and butyl acrylate monomers to obtain a cellulose grafted primary polymer;
[0079] Step 3: heating the primary polymer obtained in step 2 to 80-85° C. under stirring, adding γ-methacryloxypropyltrimethoxysilane when blue light appears, and copolymerizing for 15-30 minutes to obtain a copolymer emulsion;
[0080] Step 4: spray the copolymer emulsion obtained in step 3 onto talc powder and mix evenly, extrude water-containing talc powder particles through a granulator, and dry at 120-160° C. to obtain the carrier-free talc powder particles of the present invention.
[0081] Embodiment 3:
[0082] As an example of the preparation method of the present invention, it comprises the following steps:
[0083] Step 1: Weigh the following raw materials in parts by weight respectively: 1000 parts of talc (D50 < 1.5 microns), 350 parts of water, 2.5 parts of carboxymethyl cellulose, 1.5 parts of methacrylic acid monomer, 1.5 parts of acrylamide monomer, 8 parts of butyl methacrylate monomer, 2 parts of octadecyl methacrylate, 0.8 parts of γ-methacryloxypropyltrimethoxysilane, and 0.08 parts of potassium persulfate;
[0084] Step 2: dissolving carboxymethyl cellulose in water, adding potassium persulfate initiator, stirring and heating to 65-70°C, and then adding acrylamide, methacrylic acid, butyl methacrylate, and octadecyl methacrylate monomers to obtain a cellulose grafted primary polymer;
[0085] Step 3: heating the primary polymer obtained in step 2 to 80-85° C. under stirring, adding γ-methacryloxypropyltrimethoxysilane when blue light appears, and copolymerizing for 15-30 minutes to obtain a copolymer emulsion;
[0086] Step 4: spray the copolymer emulsion obtained in step 3 onto talc powder and mix evenly, extrude water-containing talc powder particles through a granulator, and dry at 120-160° C. to obtain the carrier-free talc powder particles of the present invention.
[0087] Embodiment 4:
[0088] As an example of the preparation method of the present invention, it comprises the following steps:
[0089] Step 1: Weigh the following raw materials in parts by weight respectively: 1000 parts of talc (D50 < 1.1 μm), 400 parts of water, 1.5 parts of sodium carboxymethyl cellulose, 1.5 parts of hydroxypropyl methylcellulose, 1 part of methacrylic acid monomer, 1.5 parts of acrylamide monomer, 0.5 parts of acrylic acid monomer, 7 parts of methyl acrylate monomer, 3 parts of butyl methacrylate monomer, 3 parts of dodecyl methacrylate, 0.5 parts of vinyl triethoxy silane, 0.5 parts of γ-methacryloxypropyl trimethoxy silane, and 0.1 parts of ammonium persulfate;
[0090] Step 2: dissolving sodium carboxymethyl cellulose and hydroxypropyl methyl cellulose in water, adding ammonium persulfate initiator, stirring and heating to 65-70° C., and then adding methacrylic acid, acrylamide, acrylic acid, methyl acrylate, butyl methacrylate, and dodecyl methacrylate monomers to obtain a cellulose grafted primary polymer;
[0091] Step 3: heating the primary polymer obtained in step 2 to 80-85° C. under stirring, adding vinyl triethoxysilane and γ-methacryloxypropyl trimethoxysilane when blue light appears, and copolymerizing for 15-30 minutes to obtain a copolymer emulsion;
[0092] Step 4: spray the copolymer emulsion obtained in step 3 onto talc powder and mix evenly, extrude water-containing talc powder particles through a granulator, and dry at 120-160° C. to obtain the carrier-free talc powder particles of the present invention.
[0093] Embodiment 5:
[0094] As an example of the preparation method of the present invention, it comprises the following steps:
[0095] Step 1: Weigh the following raw materials in parts by weight respectively: 1000 parts of talc (D50 < 0.8 μm), 400 parts of water, 3 parts of methyl cellulose, 0.5 parts of methacrylic acid monomer, 2 parts of acrylamide monomer, 6 parts of ethyl acrylate monomer, 4 parts of butyl methacrylate monomer, 2 parts of octadecyl methacrylate monomer, 0.8 parts of vinyl triethoxysilane, and 0.08 parts of potassium persulfate;
[0096] Step 2: dissolving methyl cellulose in water, adding potassium persulfate initiator, stirring and heating to 65-70° C., and then adding methacrylic acid, acrylamide, ethyl acrylate, butyl methacrylate monomer, and octadecyl methacrylate monomer to obtain a cellulose grafted primary polymer;
[0097] Step 3: heating the primary polymer obtained in step 2 to 80-85° C. under stirring, adding vinyl triethoxysilane when blue light appears, and copolymerizing for 15-30 minutes to obtain a copolymer emulsion;
[0098] Step 4: spray the copolymer emulsion obtained in step 3 onto talc powder and mix evenly, extrude water-containing talc powder particles through a granulator, and dry at 120-160° C. to obtain the carrier-free talc powder particles of the present invention.
[0099] Comparative Example 1
[0100] Compared with the talc particles obtained by ungrafted copolymerization of cellulose, water-soluble acrylic monomers, acrylate monomers and olefinic silane coupling agents, it is equivalent to simply adding a binder and a modifier on the basis of wet granulation in the prior art.
[0101] Step 1: Weigh the following raw materials in parts by weight respectively: 1000 parts of talc (D50 < 4 microns), 250 parts of water, 1.5 parts of sodium carboxymethyl cellulose, 1 part of acrylamide monomer, 4 parts of butyl methacrylate monomer, 0.5 parts of vinyl trimethoxy silane coupling agent, and 0.05 parts of potassium persulfate;
[0102] Step 2: Add acrylamide monomer to 100 parts of water, add 0.025 parts of potassium persulfate initiator, stir and heat to 65-70°C, and polymerize for 20 minutes to obtain polyacrylamide;
[0103] Step 3: Add butyl methacrylate monomer to 150 parts of water, add 0.025 parts of potassium persulfate initiator, raise the temperature to 80-85° C. under stirring, and polymerize for 20 minutes to obtain polybutyl methacrylate;
[0104] Step 4: mix sodium carboxymethyl cellulose, vinyl trimethoxysilane coupling agent, polyacrylamide obtained in step 2, and polybutyl methacrylate obtained in step 3, spray them into talc powder and mix them evenly, extrude water-containing talc powder particles through a granulator, and dry them at 120-160° C. to obtain ungrafted copolymerized carrier-free talc powder particles.
[0105] Comparative Example 2
[0106] Compared with talc particles obtained directly from cellulose.
[0107] Step 1: Weigh the following raw materials in parts by weight: 1000 parts of talc (D50 < 4 microns), 250 parts of water, and 1.5 parts of sodium carboxymethyl cellulose;
[0108] Step 2: dissolve sodium carboxymethyl cellulose in 250 parts of water, spray it into the talc powder and mix it evenly, extrude the talc powder particles containing water through a granulator, and dry it at 120-160° C. to obtain cellulose-containing carrier-free talc powder particles.
[0109] Comparative Example 3
[0110] The results were compared with talc particles obtained by copolymerization of water-soluble acrylic monomers, acrylate monomers and vinyl silane coupling agents without cellulose grafting.
[0111] Step 1: Weigh the following raw materials in parts by weight respectively: 1000 parts of talc (D50 < 4 microns), 250 parts of water, 1 part of acrylamide monomer, 4 parts of butyl methacrylate monomer, 0.5 parts of vinyl trimethoxy silane coupling agent, and 0.05 parts of potassium persulfate;
[0112] Step 2: adding potassium persulfate initiator to 250 parts of water, stirring and heating to 65-70° C., and then adding acrylamide and butyl methacrylate monomers to obtain a primary polymer of acrylamide and butyl methacrylate;
[0113] Step 3: heating the primary polymer obtained in step 2 to 80-85° C. under stirring, adding a vinyl trimethoxy silane coupling agent when blue light appears, and copolymerizing for 15-30 minutes to obtain a copolymer emulsion;
[0114] Step 4: spray the copolymer emulsion obtained in step 3 onto talc powder and mix evenly, extrude water-containing talc powder particles through a granulator, and dry at 120-160° C. to obtain carrier-free talc powder particles without cellulose grafting.
[0115] Experimental example
[0116] Stirring powder crushing rate test: weigh 20 grams of talcum powder particles and add them into a 500 ml round-bottom flask. Set the mechanical stirring speed to 250 rpm and stir for 3 minutes. Sieve out the powder with a 50-mesh sieve, weigh the powder, and calculate the percentage of powder.
[0117] Crushing load-bearing capacity test: Select talcum powder particles and spread them into an area of 1 cm × 1 cm, cover the weight tray, stack weights until the particles break, and record the maximum load-bearing capacity.
[0118] Lipophilic dispersibility test: weigh 0.5 g of talc particles into a 15 ml sample bottle, add 10 g of long-chain alkane base oil, ultrasonically disperse for 3 minutes, let stand to observe the powder sedimentation, and compare the lipophilic dispersibility.
[0119] Elution test of coating: weigh 5 grams of talcum powder particles, add 50 ml of water to a beaker, ultrasonically disperse for 5 minutes, pour into a centrifuge tube and centrifuge. The sediment at the bottom of the centrifuge tube is dissolved in 50 ml of ethanol, ultrasonically dispersed for 5 minutes, centrifuged again, and dried. Compare the lipophilic dispersibility test before and after elution. If the sedimentation is basically the same, it means that the coating on the surface of the talcum powder has not been eluted, otherwise it has been eluted. Centrifugal speed: 2000 rpm, centrifugal time: 15 minutes.
[0120] The examples and comparative examples were tested for stirring powder breaking rate, crushing bearing weight, lipophilic dispersibility, and coating elution. The results are shown in Table 1:
[0121] Table 1
[0122] Talc granules Mixing powder rate Crushing load Lipophilic dispersibility Elution of coating Example 1 9% 850g better Not eluted Example 2 7% 900g better Not eluted Example 3 6% 950g better Not eluted Comparative Example 1 27% 600g generally Elution Comparative Example 2 29% 550g Difference Elution Comparative Example 3 66% 250g good Not eluted
[0123] As can be seen from Table 1, Examples 1-3 of the present invention all have lower stirring powder breakage rate, higher breaking weight, better lipophilic dispersibility and the coating is firm and not easy to be eluted.
[0124] Compared with Example 1 of the present invention, in Comparative Example 1, cellulose, acrylamide, acrylate, and vinyl silane coupling agent are not graft copolymerized, and the powder breakage rate of the obtained particles after molding is increased by 2 times, the bearing capacity is reduced by 250g, the lipophilic dispersibility is reduced by two levels, and the coating is easy to fall off, indicating that the multi-graft copolymerization reaction of the preparation method of the present invention can greatly improve the various properties of talc particles;
[0125] In Comparative Example 2, the talc particles obtained by copolymerizing cellulose directly without adding water-soluble acrylic monomers, acrylic ester monomers and vinyl silane coupling agents have a powder breakage rate of nearly 30% and a load-bearing capacity of less than 600 g. The cellulose coated on the surface of the talc is also very easy to fall off. In particular, the lipophilic dispersibility is reduced by four levels compared with Example 1 of the present invention, indicating that the copolymerization of water-soluble acrylic monomers, acrylic ester monomers and vinyl silane coupling agents added in the present invention significantly improves the lipophilic dispersibility of the talc particles.
[0126] In Comparative Example 3, the particles obtained by using only acrylamide, acrylate, and vinyl silane coupling agent copolymer without adding cellulose have a lower lipophilic dispersibility after molding than that of Example 1 of the present invention, and the copolymer coating is not easy to elute, but the powder rate is as high as 66% and the bearing weight is the lowest. The particle molding is very unstable, indicating that the cellulose added in the present invention to participate in the graft copolymerization can greatly improve the stability of the particle molding.
[0127] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments, examples and features of the different embodiments and examples described in this specification without contradiction, and these combinations or combinations shall all fall within the scope summarized by the present invention.
[0128] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of information available through public channels and in combination with the technical inspiration provided by the present application documents.
Claims
1. A carrier-free talcum powder particle, characterized in that: The components include the following by weight: 1000 parts of talc, 1-3 parts of cellulose, 1-3 parts of water-soluble acrylic monomer, 3-13 parts of acrylate monomer, 0.5-1 part of vinyl silane coupling agent; The water-soluble acrylic monomer is any one of acrylic acid, sodium acrylate, methacrylic acid, sodium methacrylate, acrylamide, and methacrylamide, or a mixture of any two or more thereof; The acrylic acid ester monomer is any one of methyl acrylate, ethyl acrylate, butyl acrylate, dodecyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, dodecyl methacrylate, and octadecyl methacrylate, or a mixture of any two or more thereof; The preparation method of carrier-free talcum powder particles comprises the following steps: Step 1, weigh the following raw materials in parts by weight respectively: 1000 parts of talc, 200-400 parts of water, 1-3 parts of cellulose, 1-3 parts of water-soluble acrylic monomer, 3-13 parts of acrylate monomer, 0.5-1 parts of vinyl silane coupling agent, and 0.05-0.1 parts of initiator; Step 2: dissolving cellulose in 200-400 parts of water, adding an initiator, stirring and heating to 65-70° C., and then adding a water-soluble acrylic monomer and an acrylate monomer to obtain a cellulose grafted primary polymer; Step 3, heating the primary polymer obtained in step 2 to 80-85° C. under stirring, adding an olefinic silane coupling agent when blue light appears, and copolymerizing for 15-30 minutes to obtain a copolymer emulsion; Step 4: spray the copolymer emulsion obtained in step 3 onto the talc powder and mix evenly, extrude the hydrotalc powder particles through a granulator, and dry at 120-160° C. to obtain the carrier-free talc powder particles.
2. The carrier-free talc powder particles according to claim 1, characterized in that: The sedimentation particle size D50 of the talcum powder is less than 5 microns.
3. The carrier-free talc powder particles according to claim 1, characterized in that: The cellulose is any one of carboxymethyl cellulose, sodium carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose and methyl cellulose, or a mixture of any two or more thereof.
4. The carrier-free talc powder particles according to claim 1, characterized in that: The vinyl silane coupling agent is any one of vinyl trimethoxy silane, vinyl triethoxy silane and γ-methacryloxypropyl trimethoxy silane or a mixture of any two or more thereof.
5. The carrier-free talc powder particles according to claim 1, characterized in that: The initiator is any one of potassium persulfate, sodium persulfate and ammonium persulfate.
Citation Information
Patent Citations
Preparation method of carrier-free talcum powder master batch
CN101792536A
Aqueous binder for lithium ion battery, preparation method therefor and use thereof
US20180248191A1